Accounting for elite indoor 200 m sprint results - Usherwood, J. R.; Wilson, A. M. (Biology letters, 2006)
Times for indoor 200 m sprint races are notably worse than those for outdoor races. In addition, there is a considerable bias against competitors drawn in inside lanes (with smaller bend radii). Centripetal acceleration requirements increase average forces during sprinting around bends. These increased forces can be modulated by changes in duty factor (the proportion of stride the limb is in contact with the ground). If duty factor is increased to keep limb forces constant, and protraction time and distance travelled during stance are unchanging, bend-running speeds are reduced. Here, we use results from the 2004 Olympics and World Indoor Championships to show quantitatively that the decreased performances in indoor competition, and the bias by lane number, are consistent with this `constant limb force` hypothesis. Even elite athletes appear constrained by limb forces.